The effect of tutor-specific and other motivational factors on student retention on Icelandic Online. Issue 5 (26th July 2021) - Friðriksdóttir, Kolbrún
Abstract: This article presents an analysis of tracking and survey data collected over eight years on 400 users of one of seven Icelandic Online ( IOL ) courses: IOL 2 ; an open online program in Icelandic as a second language. The course is offered in three delivery modes; blended, distance, and open self-directed mode. This article introduces the second phase of a three-tiered mixed-method study and follows up previous findings on IOL that drew on tracking data from 43, 000 learners, which revealed overall low completion rates and that the blended mode is more effective in retaining learners than other modes (Friðriksdóttir, 2018 ). The main goal of the current study is to identify factors which may affect student retention on IOL, and which may explain why the blended mode is more effective. This study attempts to assess whether (a) the initial goal to complete a course and (b) certain tutor-specific factors influence retention, and also to investigate (c) self-reported motives that drive learners towards completing. The findings reveal that the intent to complete is a significant predictor of course completion and that the majority of blended learners had the initial goal of completing. Furthermore, the study illuminates that most of the learners in the tutorial modes report that tutor-specific factors were important in motivating them. Finally, course completers report diverse reasons for completion; the majority of the blended learners are driven in their goal to complete by the credits offered.